Study of Jet Quenching in Relativistic Heavy-Ion Collisions - Canedo, Fabio de Moraes (2020)
In this work, we investigate possible impacts that the behavior of the Quark-Gluon Plasma might have on Jet Observables. We choose JEWEL (Jet Evolution With Energy Loss) for this study. We have coupled JEWEL with TRENTo and also with MC-KLN+vUSPhydro for sim- ulations. The simulations were performed for PbPb collisions at sN N = 2.76 TeV in the 0 10% centrality class. We have found that jet shape observables are mainly unchanged by the inclusion of realistic hydrodynamics and initial conditions in these settings. We also made calculations for the jet v2. In this case, we have found that initial conditions do not affect this observable. In the case of realistic hydrodynamics, there is an improvement in the description of data.